Influence, Effectiveness and Language Policy A Political Action Workshop - McGuinness, Karen Lee.; Edwards, J. David; Joint National Committee for Languages, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
A model is provided for a political action workshop to educate individuals in the political process and productive participation. The workshop begins with a quiz designed to make the participant recognize the inadequacy of his political involvement and of political involvement in the country in general. A segment on the legislative and policy process includes an outline of the development of a piece of legislation, discussion of the political nature of the process, study of the budget process, and examination of other impact points, such as appointments, regulations, and elections. An exercise follows that has participants analyze a specific piece of legislation, examine the importance and effects of mail in the process, and write a letter intended to influence the course of the legislation. A segment on affecting legislation considers the roles of these elements: information, action, organization, knowledge, and involvement. A concluding, organizational segment on building a network discusses identifying specific political needs, looking at the record, building networks, and beginning action. In this stage, participants are encouraged to make specific commitments to action. Worksheets for various segments of the workshop are appended. (MSE)
ERIC Note: Prepared for the Council for Languages and Other International Studies. Developed for TESOL's (Teachers of English to Speakers of Other Languages) Summer Institute (New York, NY, July 24-26, 1981).
Community.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Activism; Educational Policy; Legislation; Networks; Politics; Power Structure; Public Policy; Second Language Instruction; Guides, Non-Classroom.